Environmental impact of livestock production in Northern Ghana: A preliminary assessment - Ansah, Terry; Cudjoe, Shedrack; Dari, Prosper S.; Van Der Hoek, Rein (2025)
The case study conducted in the Savanna agro-ecological zone focused on two communities: Tindan in the Northern Region and Bussie in the Upper-West Region. Various biophysical, environmental, and climate impacts were assessed using the CLEANED tool, relying on interviews with farmers, literature, and expert knowledge.